Determining Key Performance Indicators: Case Study at School of Business and Management ITB - Tria, Bella; Gustomo, Aurik (Journal of Business and Management, 2015)
Abstract- Organization is known as the most important and basic function of management. School of Business and Management, Institut Teknologi Bandung (SBM-ITB), is one of the most well known business and management school in the country. Today in Indonesia, the competition between different business schools has become tighter over the years. The research objective is to determine a set of alternatives of Key Performance Indicators (KPIs) for SBM-ITB since SBM-ITB currently does not have a proper system to deliver incentives for the employees, a system to develop their employees, and a system to develop their employee competencies/career. Hence a proper performance appraisal system is required to create the system. In order to create performance appraisal system, certain factors must be determined. The method use to determine the Key Performance Indicator is the steps in improving Key Performance Appraisal System, narrative analysis, and conceptual framework on determining Quantitative KPIs. The sample consists of fourteen professional staff (non-academic staff) of SBM-ITB representing their different units/division. The result of this research shows the Key Performance Appraisal for fourteen professional staffs after merging their Job Profile, ISO, RENSTRA, and conducting an interview. The result of this research is the recommended example or alternative of KPIs that can be used by SBM-ITB in determining their employee KPIs in the future, which is aim to increase the performance of their employees. The recommendation for this research is to improve and update their current job description, ISO, and RENSTRA and to further expand the KPIs for other staff in SBM-ITB. Â Keywords: key performance indicator, SBM-ITB, organization